PATIENT PRIORITY CARE APPROACH IN FRAGILE, CONFLICT AFFECTED AND VULNERABLE COUNTRIES IN SUB-SAHARAN AFRICA: A SYSTEMATIC REVIEW - Jyotishman Mukhopadhyay (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2026)
Background: Population in fragile, conflict-affected, and vulnerable (FCV) countries are increasing gradually, which brings many considerations in providing universal healthcare. Healthcare workers in FCV regions work under trying conditions with severe socio-governmental security. Studies on healthcare services in FCV countries are scarce; therefore, appraisal of published documents adopting a prudent approach is considered to identify priority care in these countries. Purpose: This research aims to weigh up information on safe healthcare measures in FCV regions by analysis of available literature to elicit facts on safer care. Methods: Related papers were searched on the basis of ‘Reduce Avoidable Harm’ as advocated by WHO among FCV countries through search engines utilising Google Scholar from December 2023 to April 2024. Four criteria on ‘Reduce Avoidable Harm’ and five criteria on ‘Prudency selection’ were categorised using information available in literature. Twenty-two articles were considered and analysed in May-June 2024. Results: The majority of studies (36.4%) documented ‘Infection Prevention & Control’ as important; however, Context Specific Risk Management (27.3%) (CSRM) to prevent maternal & child mortality was found having higher prudency score in generalisability, feasibility, effectiveness, outcome and representativeness. Since low-middle-income countries (LMICs) are stricken with problems of high mother-child mortality, as also happens in FCV-LMICs. Conclusion: CSRM to prevent mother-child mortality was observed significantly pertinent, very alarming in LMICs and contributing around 60% of global maternal-child mortality. An urgent need is contemplated to introduce evidence-based specialist knowledge, guidance on safe healthcare including education, training, patient identification, and risk management for stakeholders.